SAÚDE MENTAL DE INTERNAUTAS UNIVERSITÁRIOS - Marcos, Vanessa Pasvenskas (2011)
This study aimed to assess the mental health of college internet users. This is a cross-sectional research and quantitative. The study included 150 internet users, genders, male and female, aged between 17 and 53 years old, students from several graduate courses at the college health, a single campus of a private university, located in São Bernardo do Campo on the São Paulo metropolitan area. The sample was selected by criteria of convenience, but it was considered by quota sampling to better represent the population. The instruments used were the Psychiatric Morbidity Questionnaire for Adults (QMPA) and an additional questionnaire designed to characterize the sample. After collection, the data were statistically treated and released. The results showed the prevalence of mental health in 58% of college Internet users. Among participants who had symptoms of psychiatric morbidity (42%) were the most prevalent symptoms of mood disorder, anxiety, somatization, depression and irritability, symptoms, commonly referred to as minor psychiatric disorders. Were considered heavy users by use the Internet for over 60 hours per month, 55% of Internet users studied. However these symptoms of psychiatric morbidity showed no differentiation between types of users (heavy and light), prevailed in both cases the mental health evaluation. The hours of Internet access were considered one of the signs of pathological Internet use, but insufficient to diagnose the pathological use. The pathological Internet use was present in 57% of Internet users, by using the Internet to the detriment of other aspects of their lives. The symptoms of psychiatric morbidity showed significant positive correlations with the issues on the pathological use of the Internet. These results suggest that the pathological use of the internet reveals itself as a new field of expression of psychiatric morbities known. Thus, the Internet does not appear as a risk factor for mental health of its users. It would be an amplifier, a tool that would facilitate the expression of such pathological behaviors, that come from existing disorders as well as the use of various other social practices, which can become pathological manifestations of different disorders by the individual.